Empirical nexus between Chinese investment under China–Pakistan Economic Corridor and economic growth: An ARDL approach - Sabeeh Ullah; Shahzad Hussain; Budi Rustandi Kartawinata; Zia Muhammad; Rosa Fitriana (Cogent Business & Management, 2022)
This study examines the causality between Chinese Investment under China-Pakistan Economic Corridor and economic growth in Pakistan by using the Autoregressive distributed lag estimation framework. For this purpose, quarterly time series data ranging from 2009 to 2018 were used. In short run, results failed to establish causality from Chinese Foreign Direct Investment to Economic Growth, while a unidirectional causality was found from economic growth to Chinese Foreign Direct Investment. However, results of this study confirm that the variables of interest are bound together in the long run only when Chinese Foreign Direct Investment is the dependent variable, indicating that enhanced economic growth attracts more Foreign Direct Investment in Pakistan. Results of this study have important implications for economists and policymakers to make policies alongside China Pakistan Economic Corridor in order to ensure that the potential spillovers from the inflow of Chinese Foreign Direct Investment in the shape of China Pakistan Economic Corridor infrastructure projects create domestic spillover. Moreover, the insignificant effect of Chinese Foreign Direct Investment on the economic growth of Pakistan in the short run is due to the real challenges that Pakistan faces due to access to credit and state capacity to sustain economic growth. Therefore, it is recommended that government should formulate policies for technologically demanding sectors to bring diversity in the products and increase exports.
Keywords: 650; ARDL co-integration; China; economic growth; foreign direct investment; Pakistan